Wpływ ilości spożywanych posiłków na wartość wskaźnika BMI = Influence amount of food meals for BMI - Nalepa, Dorota; Weber, Dorota; Rogala, Renata; Charzyńska-Gula, Marianna (Journal of Education, Health and Sport, 2016)
Nalepa, Dorota, Weber, Dorota, Rogala, Renata, Charzyńska-Gula, Marianna. Wpływ ilości spożywanych posiłków na wartość wskaźnika BMI = Influence amount of food meals for BMI. Journal of Education, Health and Sport. 2016;6(3):48-61. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47438 http://ojs.ukw.edu.pl/index.php/johs/article/view/3400 https://pbn.nauka.gov.pl/works/719646 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. WPŁYW ILOŚCI SPOŻYWANYCH POSIŁKÓW NA WARTOŚĆ WSKAŹNIKA BMI INFLUENCE AMOUNT OF FOOD MEALS FOR BMI Dorota Nalepa1, Dorota Weber2, Renata Rogala3, Marianna Charzyńska-Gula4 1Oddział Neurologii Wojewódzkiego Szpitala Specjalistycznego im. Stefana Kardynała Wyszyńskiego w Lublinie, doktorantka Katedry Nefrologii Uniwersytetu Medycznego w Lublinie, email: nalepad1@wp.pl, Tel. 668748836 2Absolwentka Kierunku Pielęgniarstwo Warszawski Uniwersytet Medyczny 3Doktorantka studiów doktoranckich w Zakładzie Kwalifikowanej Pomocy Medycznej z Pracownią Ratownictwa Medycznego Uniwersytetu Medycznego w Lublinie 4Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu Streszczenie. Celem badań była ocena wpływu ilości spożywanych posiłków w ciągu dnia na wskaźnik BMI. Metody i materiał. Badania przeprowadzono w okresie styczeń – luty 2015 roku w jednej z lubelskiej przychodni. Do badań zakwalifikowano 148 respondentów. Zastosowaną metodą w badaniach był sondaż diagnostyczny, a wykorzystaną techniką kwestionariusz wywiadu przeprowadzony wśród respondentów, w którym wykorzystano: metryczkę, wywiad i badanie antropometryczne obejmujące pomiar wysokości i masy ciała, na podstawie których określono wskaźnik masy ciała BMI (ang. Body Mass Index). Wyniki. Ilość dziennie spożywanych posiłków przez respondentów jest różna. Biorąc pod uwagę wiek respondentów, który traktowany jest jako przynależność do jednej z grup, uczących się lub pracujących zauważono że osoby uczące się najczęściej spożywają 4-5 posiłki zadeklarowało tak 40 badanych (58,8%), 3 posiłki spożywa 21 osób (30,9%). Od 6- do 8 posiłków dziennie spożywa 5 osób (7,4%) w tej grupie zaś 2osoby zjadają tylko 2 posiłki (2,9%). Wnioski. Na podstawie przeprowadzonych badań własnych sformułowano następujące wnioski: - na regularność spożywania posiłków nie mają wpływu wiek i płeć respondentów, istnieje natomiast istotny związek między miejscem zamieszkania a ilością spożywanych posiłków. - na wartość wskaźnika BMI ma wpływ wiek i płeć respondentów. Osoby uczące się oraz kobiety przywiązują uwagę do swojej wagi i BMI częściej osiąga granice wskazujące na prawidłową masę ciała. - pierwsze śniadania są spożywane przez większość respondentów i nie mają na to wpływu czynniki społeczno - demograficzne takie jak wiek, płeć i miejsce zamieszkania. Słowa kluczowe: otyłość, wskaźnik BMI. Summary The aim of the investigation is to assess the influence of the number of consumed meals upon the BMI. Methods and materials The research was conducted from January to February 2015 in a medical clinic in Lublin. 148 respondents were qualified for the research. The applied method was a diagnostic survey carried out among the respondents, which used: the birth certificate, interview as well as anthropometric measurements, covering the body height and body mass. In this way, the Body Mass Index was determined. Findings The number of meals, consumed daily, varied. Taking into account the age of the respondents, which served to divide the persons into different groups – studying or working ones, it was observed that students usually consume four to five meals, as declared by 40 examined persons (58.8%). 21 persons consumed three meals (30.9%), 5 persons ate between six and eight meals per day (7.4%), and only two persons consumed two meals (2.9%). Conclusions - On the basis of the conducted research, the author was able to draw the following conclusions: - the age or gender of the respondents does not influence the regularity of consumed meals; there is a significant link, however, between the place of living and the number of the consumed meals. - the age or gender of the respondents exerts an impact upon the BMI. Studying persons, women treat their weight as important. In this case, BMI comes close to proper Body Mass values. - the first meal (breakfast) is consumed by the majority of the respondents and is not affected by such social-demographic factors as age, gender or place of living. Key words: obesity, BMI (Body Mass Index).